Fundamentals of guided-wave optoelectronic devices - Chang, William S. C. 1931- (Cambridge University Press, 2010)
Optoelectronic guided-wave devices are used in a wide range of optical fiber communication and optoelectronic systems. In such networks, the electrical and the optical characteristics of guided-wave devices, and the interplay between them, have a profound effect on system design and overall performance. Uniquely, this book combines both the optical and electrical behavior of guided-wave optoelectronic devices so that the interwoven properties, including interconnections to external components, are easily understood. It provides the key concepts and analytical techniques that readers can apply to current and future devices. It also presents the impact of material properties on guided-wave devices, and emphasizes the importance of time-dependent interactions between electrical and optical signals. This is an ideal reference for graduate students and researchers in electrical engineering and applied physics departments, as well as practitioners in the optoelectronics industry
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Optoelectronic devices; Integrated optics; Optoelektronisches Bauelement; Lichtwellenleiter